1981
DOI: 10.1104/pp.67.3.449
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Testa in Preventing Cellular Rupture During Imbibition of Legume Seeds

Abstract: Studies with the seeds of soybean, navy bean, pea, and peanut were made to determine the extent of leakage of intracellular enzymes during imbibition. Embryos with intact testae from all four species were found to leak detectable activities of either intracellular enzymes of the cytosol (glucose--phosphate dehydrogenase) or and that, with removal of the testa from seeds, the "leakage phenomenon" is enhanced (14,32). The amount of leakage during imbibition has been shown to correlate negatively with viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
65
0
3

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 19 publications
5
65
0
3
Order By: Relevance
“…Nordin (1984) demonstrated that the seed coat acted as a semi-permeable membrane, permitting the entry of water and certain solutes while restricting others. Duke and Kakefuda (1981) compared the seeds of four legumes with or without seed coats and found that the embryonic cells of soybean and navy bean seeds without seed coats ruptured when submerged. Matsui et al (1996) demonstrated, using seeds without a seed coat or aleurone layer, that the aleurone layer signifi cantly alleviated the extent of fl ooding damage in soybean.…”
mentioning
confidence: 99%
“…Nordin (1984) demonstrated that the seed coat acted as a semi-permeable membrane, permitting the entry of water and certain solutes while restricting others. Duke and Kakefuda (1981) compared the seeds of four legumes with or without seed coats and found that the embryonic cells of soybean and navy bean seeds without seed coats ruptured when submerged. Matsui et al (1996) demonstrated, using seeds without a seed coat or aleurone layer, that the aleurone layer signifi cantly alleviated the extent of fl ooding damage in soybean.…”
mentioning
confidence: 99%
“…It has been proposed that the reason for this correlation is that seed pathogen growth may be enhanced by the presence of seed leachates (23). However, recent studies with imbibing legume seeds suggest that some loss of vigor may be due to the destruction of seed tissues and the creation of infection sites by massive cellular rupture which can occur during imbibition (7,9,11).…”
mentioning
confidence: 99%
“…Seeds with various degrees of testa integrity were used because testa integrity is a primary factor in controlling legume seed leakage and cellular damage during germination (7,11,12,21,24). Effects of temperature were studied to gain insight into the energetics of the leakage of various seed components during imbibition and effects of 4,2 were studied because of previous studies which indicate a 4iw effect on soybean seed leakage and seedling vigor (28,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although EC test results are reproducible among laboratories, some factors affect the results, such as seed size (Tao, 1978;Deswal & Sheoran, 1993), soaking temperature (Murphy & Noland, 1982), soaking period (Loeffler et al, 1988;Schmidt & Tracy, 1989), initial water content (Tao, 1978;Loeffler et al, 1988;Vieira et al, 2002), and the presence of physical damaged seeds (Tao, 1978;Duke & Kakefuda, 1981). However, all these factors can be controlled to minimize their effects.…”
Section: Introductionmentioning
confidence: 99%